Diagnosis of yeasts isolated from the oral cavity and groin area in children of Kirkuk city/Iraq - Taiba Mansour Muhammad Musleh1; Hadi Alwan Muhammad Al-Saadi (Tikrit Journal of Pure Science, 2022)
This study was conducted in the Graduate Studies Laboratory / College of Education for Pure Sciences - Kirkuk University;  200 swabs were collected from the oral and groin areas of children infected with candidiasis for both inpatients and outpatients at the Children’s Hospital, the Maternity, Gynecology and Children’s Hospital, and Azadi Teaching Hospital in Kirkuk governorate;  whose ages ranged from 1 day - 3 years for both males and females;  For a period ranging from February-2021 to March 25-2021. The immediate results of the microscopic examination showed that 152 smears (76%) were positive, while the results of culturing the smears on solid Sabouraud medium showed that 140 smears (70%) of the smears showed growth, and 60 smears (30%) of the smears showed no growth.